Devastating effect of untreated facial squamous cell carcinoma. Issue 5 (3rd September 2021) - Khalfe, Nasim; Xu, Ya; Schuele, Elizabeth May; Lin, Doris
Abstract: Skin cancer develops primarily on areas of sun-exposed skin and can typically be treated if caught early. Here, we present a case of a 57-year-old man who presented with an extremely large facial squamous cell carcinoma with resulting perineural invasion and metastasis to parotid lymph nodes because he was unable to obtain timely treatment.